Autonomous quadcopter altitude for measuring risky gases in hazard area - Wan Hasan, Wan Zuha; Bashi, Omar Ibrahim Dallal; Shafie, Suhaidi; Azis, Norhafiz; Wagatsuma, Hiroaki (Universiti Teknikal Malaysia Melaka, 2018)
The increased awareness of environmental monitoring has led to the development platforms for measuring gases concentration in the risk environment. In this paper, we focused on the altitude of quadcopter flying, not to be random but will be at a certain height depending on the application and the area of implementation for a quadcopter robot. A practical implementation is recorded to know the suitable height of flying. The quadcopter is also developed to fly manually with automatic height adjustment in order to measure gas concentration reliably.